2014
DOI: 10.1590/1677-3225v13n1a13
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of a "solvent-free" adhesive versus contemporary adhesive systems

Abstract: Aim: To compare the shear bond strength (SBS) of a solvent free self-etch adhesive with solvent containing adhesives. Methods: Forty-five human teeth were sectioned longitudinally to expose superficial dentin and substrates polished with 600-grit SiC paper. The adhesive area was isolated with a cylindrical Teflon mold 3x4 mm. Fifteen specimens were prepared for each material. Were evaluated a solvent free self-etch adhesive (Bond 1 SF), an ethanol self-etch adhesive (Futurabond M), and a water-acetone-ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…The self‐etch adhesive slightly increased surface roughness after laser ablation, and incompletely removed the smear layer following SiC pretreament. One previous study showed that All‐In‐One adhesive provided a hybrid layer and excellent penetration into the dentin tubules (Koliniotou‐Koumpia et al, ). Mild etching after the application of Vertise Flow created irregularities on enamel surfaces pretreated with laser and partly removed the smear layer on the SiC‐pretreated dentin.…”
Section: Discussionmentioning
confidence: 99%
“…The self‐etch adhesive slightly increased surface roughness after laser ablation, and incompletely removed the smear layer following SiC pretreament. One previous study showed that All‐In‐One adhesive provided a hybrid layer and excellent penetration into the dentin tubules (Koliniotou‐Koumpia et al, ). Mild etching after the application of Vertise Flow created irregularities on enamel surfaces pretreated with laser and partly removed the smear layer on the SiC‐pretreated dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Shear bond strength (SBS) is a mechanical test of the adhesive interphase that can provide an indication of the bond integrity between esthetic restorations and dentin surface. Reliable results were achieved in previous researches studying dentin-adhesives interphase (12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Introductionmentioning
confidence: 78%
“…Koliniotou-Koumpia et al evaluated a solvent free self-etch adhesive (Bond 1 SF), an ethanol self-etch adhesive (Futurabond M), and a water-acetoneethanol self-etch adhesive (Optibond All-In-One) [17]. They found that solvent free self-etch (Bond 1 SF) had lower SBS as compared to the other two groups.…”
Section: Discussionmentioning
confidence: 99%